Supporting caregivers of children born prematurely in the development of language: A scoping review. Issue 1 (21st October 2019) - Belanger, Roxanne; Leroux, Dominique; Lefebvre, Pascal
Abstract: Background: Infants born prematurely can display impairments that negatively impact the early years of their development. Compared to their peers born at term, preterm children have higher risks of cerebral palsy, sensory deficits, learning disabilities, cognitive and language deficits, as well as difficulties related to attention and behaviour. Following discharge, parents of preterm children are often supported through neonatal follow-up programs or by community health care practitioners. Through assessment and consultation, professionals foster parental resilience by teaching them about their child's development. Research shows a large volume of literature on improving outcomes for preterm infants, but less attention has been given to the impact and potential importance of education of parents regarding the care they provide from the home. Objective: A scoping review was completed to determine the best practices for early intervention in premature children regarding the development of language skills during the preschool years. Methods: The review followed the guidelines for the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA). Results: Four general themes emerged from the review and included the importance of providing (1) parental training in the care of an infant born prematurely during neonatal intensive care unit stay; (2) education on the development of language and the importance of parental responsiveness; (3) provision of activities to support child language learning; and (4) overall and ongoing monitoring and support by qualified health professionals. Conclusions: The conclusions drawn will provide guidance to health care professionals regarding the education of parents on best practices for stimulating language development in their child.